PENINGKATAN KOMPETENSI MENULIS TEKS ANEKDOT DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PESERTA DIDIK KELAS X II SMA NEGERI 1 BONTOMATENE KABUPATEN KEPULAUAN SELAYAR - Andi Agus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2015)
This research aims at describing the plan, implementation, and the improvement of anecdote teks writing competency with problem based learning model of class X II students at SMA Negeri 1 Bontomatene Kepulauan Selayar district. The kind of this research is a classroom action research. The subject of the research was class X II student of SMAN Bontomatene Kepulauan Selayar district of academi years 2014/2015 with the total of 26 student. This research was conducted in two cycles; each cycle consisted of 3 times of treatment. In implementation step, every cycle used observation sheets, knowledge test, and anecdote teks writing competency texs to collect the data and as the success benchmark of anecdote teks competency of the student based on minimal complementeness criteria (KKM) with the score of 75. The result of the research reveal that through the problem based learning model, the students’ anecdote texs writing learning process of class X II at SMAN 1 Bontomatene Kepulauan selayar district on implementation steps and learning outcomes are improve. The subject teacher is successful in formulating good lesson plan. At amplementation step, the teacher optimizes the leaming presentation auttthe students have expgrienced changing behavior to better ones. At the evaluation step, the result of anecdote text writing in cycle I by considering the aspects of content aspect, text structure, vocabularies, sentences, and mechanics, shows that the students have not yet to reach the completeness standard.